Customer profile of a summer hiking tourist: Kilpisjärvi Holiday Village & camping (Kilpisjärven Retkeilykeskus) - Alasuvanto, Janna (2023)
This research, made for JAMK University of applied sciences bachelor’s degree program in tourism management, was to conduct a customer profile of summer hiking tourists in Kilpisjärvi Holiday Village & Camping. The reason for the research was to increase understanding on this specific tourism group and to see them as a customer from the view of commissioner company. In a larger perspective, data gathered from hiking tourists in Finland is beneficial as the nature-based tourism is growing globally and nationally and it is worth to pay attention to. Kilpisjärvi as being a growing nature-based destination, understanding the consumers in the area can help the company develop their marketing, products, and services.